An analysis of vascular properties using pulse wave analysis in patients with vasovagal syncope. Issue 7 (18th June 2020) - Jang, Ji‐Hun; Park, Jin‐Hee; Ko, Kyu‐Yong; Baek, Yong‐Soo; Kwon, Sung‐Woo; Park, Sang‐Don; Shin, Sung‐Hee; Woo, Seong‐Ill; Kwan, Jun; Kim, Dae‐Hyeok
Abstract: Background: Vasovagal syncope (VVS) is a common cause of recurrent syncope. Nevertheless, the exact hemodynamic mechanism has not been elucidated. Pulse wave analysis (PWA) is widely used to evaluate vascular properties, as it reflects the condition of the entire arterial system. Hypothesis: Cardiovascular autonomic modulation may influence the hemodynamic mechanism and result in different vascular properties between VVS patients and healthy individuals. Methods: We enrolled consecutive patients diagnosed with VVS on head‐up tilt testing from January 2014 to August 2019. Healthy subjects were enrolled as the control group. We performed PWA on all participants. Using propensity score matching, we assembled a study population with similar baseline characteristics and compared hemodynamic parameters. Results: A total of 111 VVS patients (43 ± 18 years, 72 females) and 475 healthy control subjects (48 ± 13 years, 192 females) were enrolled. Compared to the healthy control subjects, the VVS patients had a higher augmentation index (AIx) adjusted to a heart rate of 75 beats per minute (AIx@HR75, 20.5 ± 13.1% vs 16.7 ± 11.9%, P = .003). After 1:1 matched comparison (111 matched control), VVS patients consistently showed higher AIx@HR75 (20.5 ± 13.1% vs 16.7 ± 12.9%, P = .02) than the matched control group. According to age distribution, VVS patients showed significantly higher AIx@HR75 (10.6 ± 11.7% vs 2.5 ± 11.1%, P = .01) in a young age (15‐33 years) group. Conclusions: VVS patients had greater arterial stiffness than healthy subjects. This is one of the plausible mechanisms of the pathophysiology of VVS.